DIGITAL TECHNOLOGY USE AND INTERGENERATIONAL INTEGRATION: THE MEDIATING ROLE OF DIGITAL LITERACY. (20th December 2022) - Park, Hayoung; Choi, Bomi; Joo, Susanna; Kim, Yoon-Myung; Kim, Hyoun K
Abstract: This study aimed to analyze the mediating effect of digital literacy on the association between digital technology use and intergenerational integration in later life. The sample included 315 older Korean adults aged 65 and above (M=68.83, SD=4.19, range=65-84) who participated in an online survey in December 2021. The participants' use of digital technology was measured by the sum of thirteen questions about how often they used each digital technology in their daily lives. Intergenerational integration was measured by the sum of thirty questions concerning awareness of understanding and empathizing with characteristics and cultures between generations to live harmoniously in the times through communication and cooperation. The mediating variable, digital literacy, was measured by the sum of thirty-five questions from the New Media Literacy Scale, asking individuals' ability to find, evaluate, and communicate information in a digital society. Age, gender, education level, household income, marital status, and living conditions were controlled for to reduce confounding effects. According to the mediation path analysis using SPSS PROCESS macro and bootstrapping, digital literacy significantly mediated the effects of digital technology use on intergenerational integration in later life; the higher the level of digital technology use, the higher the level of digital literacy, and this had a positive effect on the level of awareness of intergenerational integration among older adults. This study is significant in that it confirms the mechanism underlying the link between digital technology use and intergenerational integration and provides a new empirical model to promote intergenerational integration in terms of digital aging.